The The South Pacific Chessboard: strategic Competition Through the China-Solomon Islands Security Pact (Journal of the Spanish Institute for Strategic Studies, 2023)
In this article I will attempt to define the geostrategic chessboard of the South Pacific in the framework of power competition. To do so, I delimit the chessboard to a set of countries that share several unique characteristics; I examine the role played by each actor in this scenario, emphasizing the strategic interests and policies they have developed because of this competition. Finally, I review the events that have triggered a new power competition in the South Pacific. I argue that the security pact between China and the Solomon Islands may represent a turning point in the competition between the powers present in the region and what are the implications and responses derived from it.
Keywords: Pacific Islands; Geostrategy; Solomon Islands; China; Power competition